Theoretical analysis of atomic parameters of Sm-like and Nd-like W ions in soft x-ray region. (1st July 2022) - Singh, Narendra; Aggarwal, Sunny; Goyal, Arun
Abstract: We calculated atomic data such as energy levels, transition wavelengths, oscillator strengths and transition rates for Sm-like and Nd-like W ions. We employed flexible atomic code (FAC) in our computations. We computed fine structure levels of configurations 4f 12 5s 2, 4f 12 5s5p and 4f 13 5s for Nd-like W and configurations 4f 14 5s 2, 4f 13 5s 2 5p and 4f 12 5s 2 5p 2 for Sm-like W. We have provided transition data of electric dipole (E1) transitions and magnetic quadrupole (M2) transitions for transition 4f 12 5s 2 —4f 12 5s5p and magnetic dipole (M1) and electric quadrupole (E2) transition data for transition 4f 14 5s 2 − 4f 12 5s 2 5p 2 . We also found that spectral lines of these transitions in Sm and Nd-like W ion spectra lie in soft x-ray (SXR) region. We compared transition data of Nd-like W and excitation energies of Sm-like W ions with available theoretical and experimental results. We also discussed the effect of configuration interaction on atomic data of Nd-like W and excitation energies of Sm-like W by systematically increasing the number of configurations.